2015
DOI: 10.1111/idj.12176
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of natural tooth colour with aging in the Spanish population

Abstract: The strongest correlation was found between age and L*, then between age and h* (both inverse relationships) and then between age and a*, C* and b* (direct relationships). In addition, a similar degree of change in the colour coordinates L*, C* and h* (of 0.60 units/year on average) was observed for natural tooth colour. Knowledge of the chromatic range of natural teeth may help to choose colour for the replacement of missing elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
2
15
1
1
Order By: Relevance
“…The change detected was comparable with the color difference between 2 hue groups in the 3D shade guide (VITA Zahnfabrik, Bad Säckingen, Germany) and, therefore, slightly lower (Δ h° 2–2.4 units) than the hue change estimated on the basis of a cross‐sectional study (0.6 units/year × 8 years = 4.8 units). In contrast with previous reports, changes of lightness and chroma seem to be age‐cohort‐specific. Especially, a linear decrease of lightness and a linear increase of chroma during aging may be qualified by the recent data .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The change detected was comparable with the color difference between 2 hue groups in the 3D shade guide (VITA Zahnfabrik, Bad Säckingen, Germany) and, therefore, slightly lower (Δ h° 2–2.4 units) than the hue change estimated on the basis of a cross‐sectional study (0.6 units/year × 8 years = 4.8 units). In contrast with previous reports, changes of lightness and chroma seem to be age‐cohort‐specific. Especially, a linear decrease of lightness and a linear increase of chroma during aging may be qualified by the recent data .…”
Section: Discussioncontrasting
confidence: 99%
“…This longitudinal approach partially confirms results from a previous cross‐sectional study. A change of hue ( h °) toward red/an increase of redness ( a *) found in previous study was confirmed longitudinally for both cohorts. The change detected was comparable with the color difference between 2 hue groups in the 3D shade guide (VITA Zahnfabrik, Bad Säckingen, Germany) and, therefore, slightly lower (Δ h° 2–2.4 units) than the hue change estimated on the basis of a cross‐sectional study (0.6 units/year × 8 years = 4.8 units).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations